MEWUJUDKAN PERLINDUNGAN DATA KONSUMEN PADA PEER TO PEER LENDING MELALUI MARKET CONDUCT - Taruna Prakarsa; Muhammad Abdul Ghofur (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The present study aims to examine how Lawrence M. Friedman's legal system theory views market conduct as an ideal legal effort in realising consumer data protection in p2p lending. This research employs a doctrinal approach, utilising qualitative legal analysis through two distinct methodologies: the statute approach and the conceptual approach. The findings suggest that the pursuit of market conduct as an ideal legal effort in realising consumer data protection in peer-to-peer lending can be achieved by fulfilling three legal aspects: legal substance, legal structure, and legal culture. In essence, the most critical prerequisite is to ensure harmonisation, both in terms of principles and norms, in all regulations pertaining to consumer data protection, both vertically and horizontally. In legal structure, it is essential to delineate clear boundaries of authority for the institutions responsible for consumer data protection in p2p lending. In the context of legal culture, it is imperative to prioritise the five principles of Pancasila as a paradigm for the development of a legal culture that is congruent with the values and ideals that delineate the nation and society. This will facilitate the development of an optimal legal culture